Ultrasound-assisted Dehydration Process Applied to Red Globe Grapes for Producing Low Calorie Raisins - Laborde, Mariana Belén (2018)
In this paper the application of ultrasound was investigated as a method for improving mass transfer during the first stage of a process of osmosis combined with dehydration drying to obtain grapes reduced in high calorie sugars. Fresh grapes (Vitis vinífera L.) Red Globe variety were subjected to immersion in distilled water at room temperature with assistance ultrasound (40 kHz) using a weight ratio fruit: solvent of 1: 4, during regularly spaced intervals in the range 0-30 minutes; comparatively a control treatment without application of ultrasound (0 kHz) was conducted. Subsequently, the grapes were stabilized by drying at 70°C. The analysis of variance showed significant influence of treatment on the soluble solids content and gain at all times. The greatest sugars reductions were achieved when ultrasound was used. Process monitoring was conducted by assessing the change in the sugar content of grapes by refractometry (°Brix), and confirming the results by HPLC. The best treatment that significantly reduced (p <0.05) the content of the major sugars in fresh fruit (30% fructose and 27% glucose) turned out to be 25 minutes immersion assisted by ultrasound.